Endoscopic Papillectomy for Ampullary Tumors - Kwang Bum Cho (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Ampullary tumors originate from the ampulla of Vater and are often discovered incidentally during an upper endoscopy. These tumors usually occur sporadically and may be benign or malignant in nature. Tumor growth clinically presents with cholestasis, pancreatitis, and bleeding. Patients with ampullary adenomas are often asymptomatic; however, removal of these lesions is recommended in view of their malignant potential. Following advances in endoscopic techniques and the accumulation of experience, considering high recurrence, mortality, and morbidity rates associated with surgery, endoscopic papillectomy may be useful as first-line treatment for adenomatous lesions with ambiguous malignant changes or focal intraepithelial carcinoma. Although it is relatively safe and easy to perform, the operation is a high-level procedure that may be associated with serious complications. It should be performed by an experienced endoscopist at a well-equipped hospital/center with emergency facilities and support personnel. Accurate resection is associated with high treatment success rates. Most complications are mild and can be treated medically. Pancreatitis is the most common complication, and pancreatic duct stenting is useful for prophylaxis. Recurrence may occur, and is more frequently observed during segmental resection; therefore, close periodic follow-up is essential. Although there are no unified indications or guidelines for endoscopic papillectomy, endoscopic papillectomy may be safe and effective for management of ampullary adenomas. Careful patient selection and follow-up are mandatory.